Effects of Including Gender Pronoun Questions in Surveys - Palanica, Adam; Lopez, Luke; Gomez, Amy; Fossat, Yan (Frontiers in Psychology, 2022)
This research examines whether the mere presence of asking about gender pronouns (e.g., she/her, he/him, they/them, ze/zir) in a survey enhances participants’ attitudes and satisfaction of answering the questions. A large sample (N = 1511) of heterosexual, cisgender, and LGBTQIA+ participants across the US were surveyed an online “personality test” (as a deception), with the real purpose of examining whether asking a pronoun question enhanced their perceptions of the survey. Three demographic groups were included: i) heterosexual–cisgender (n = 503), ii) gay–cisgender (n = 509), and iii) genderqueer (trans, non-conforming, other, n = 499). Half of each group were randomly given either a survey that included a gender pronoun question (test) or not (control), and then all rated their perceptions of the survey questions. For participants who identified as heterosexual or gay, no major differences were found between survey conditions. However, participants who identified as genderqueer experienced significant increases of satisfaction, comfort level, and perceived relevance of the questions when given a survey that asked their gender pronouns versus the survey that did not. These findings have implications for any surveys that ask about personal demographics, and suggest that any form of written communication should include clarity about gender pronouns.